Answer:
Probabilities
Likely to happen (L) Unlikely to happen (U)
a. 4/5 5/8
b. 3/5 3/8
c. 4/5 4/7
d. 0.3 0.09
e. 5/6 and 4/5 2/3
Step-by-step explanation:
Probabilities in Percentages:
a. The probability of 4/5 = 80% and 5/8 = 62.5%
b. The probability of 3/8 = 37.5% and 3/5 = 60%
c. The probability of 4/5 = 80% and 4/7 = 57%
d. The probability of 0.3 = 30% and 0.09 = 9%
e. The probability of 2/3 = 67% and 4/5 = 80% and 5/6 = 83%
b) To determine the relative values of the fractional probabilities, it is best to reduce them to their fractional or percentage terms. When this is done, the relative sizes become obvious, and then, comparisons can be made.
Answer:
0.06
Step-by-step explanation:
probability of multiple of 6= 0.2
probability of multiple of 4= 0.3
0.2 * 0.3 = 0.06
The amount of money Ben had to begin with after spending 1/6 and 1/2 of it is 57 dollars.
<h3>How to find the how much money he had with an equation?</h3>
let
x = amount he had to begin with
He spent 1/6 of his money on a burger, fries, and a drink. Therefore,
amount spent on burger, fries, and a drink = 1 / 6 x
Hence,
amount he had left = x - 1 / 6 x =6x - x /6 = 5 / 6 x
Then he spent half of the money he had left.
1 / 2(5 /6 x) = 5 + 8.25 + 10.50
5 / 12 x = 23.75
cross multiply
5x = 23.75 × 12
5x = 285
divide both sides by 5
x = 285 / 5
x = 57
Therefore, the amount of money he have to begin with is $57.
learn more on equation here: brainly.com/question/5718696
Answer:
- (-16x² +10x -3) +(4x² -29x -2)
- (2x² -11x -9) -(14x² +8x -4)
- 2(x -1) -3(4x² +7x +1)
Step-by-step explanation:
I find it takes less work if I can eliminate obviously wrong answers. Toward that end, we can consider the constant terms only:
- -3 +(-2) = -5 . . . . possible equivalent
- -10 -5 = -15 . . . . NOT equivalent
- 3(-5) -2(5) = -25 . . . . NOT equivalent
- -9 -(-4) = -5 . . . . possible equivalent
- -7 -(-5) = -2 . . . . NOT equivalent
- 2(-1) -3(1) = -5 . . possible equivalent
Now, we can go back and check the other terms in the candidate expressions we have identified.
1. (-16x² +10x -3) +(4x² -29x -2) = (-16+4)x² +(10-29)x -5 = -12x² -19x -5 . . . OK
4. (2x² -11x -9) -(14x² +8x -4) = (2-14)x² +(-11-8)x -5 = -12x² -19x -5 . . . OK
6. 2(x -1) -3(4x² +7x +1) = -12x² +(2 -3·7)x -5 = -12x² -19x -5 . . . OK
All three of the "possible equivalent" expressions we identified on the first pass are fully equivalent to the target expression. These are your answer choices.
(2,7) is going to be the answer for that